2022
DOI: 10.1021/acschemneuro.2c00365
|View full text |Cite
|
Sign up to set email alerts
|

Identifying an Optimal Neuroinflammation Treatment Using a Nanoligomer Discovery Engine

Abstract: Acute activation of innate immune response in the brain, or neuroinflammation, protects this vital organ from a range of external pathogens and promotes healing after traumatic brain injury. However, chronic neuroinflammation leading to the activation of immune cells like microglia and astrocytes causes damage to the nervous tissue, and it is causally linked to a range of neurodegenerative diseases such as Alzheimer's diseases (AD), Multiple Sclerosis (MS), Parkinson's disease (PD), and many others. While neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
92
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 18 publications
(95 citation statements)
references
References 77 publications
3
92
0
Order By: Relevance
“…While a longer-term study would be necessary to confirm a lack of T-cell response and antibody production, there is thus far no indication that Nanoligomers cause activity in the immune system (Figures and S5–S9). Recent studies have shown that human primary astrocytes treated with missense Nanoligomers show the cytokine profile as measured in a 65-plex panel similar to untreated cells, indicating the effects observed are due to sequence-specific action of Nanoligomers . This is in contrast with siRNA therapies, PNA conjugated to CPP, and lipid-encapsulated ASOs. , Nanoligomers are readily available to key organs such as the lungs, kidneys, liver, and spleen.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While a longer-term study would be necessary to confirm a lack of T-cell response and antibody production, there is thus far no indication that Nanoligomers cause activity in the immune system (Figures and S5–S9). Recent studies have shown that human primary astrocytes treated with missense Nanoligomers show the cytokine profile as measured in a 65-plex panel similar to untreated cells, indicating the effects observed are due to sequence-specific action of Nanoligomers . This is in contrast with siRNA therapies, PNA conjugated to CPP, and lipid-encapsulated ASOs. , Nanoligomers are readily available to key organs such as the lungs, kidneys, liver, and spleen.…”
Section: Discussionmentioning
confidence: 99%
“…Another major advantage of Nanoligomers discovery engine is the ability to target gene(s) of interest on demand to up- or downregulate expression. Multiple studies have shown the use of Nanoligomers to target the library of immunological genes including interleukin-1β, TNF receptor 1, inflammasome (NLRP1), granulocyte-macrophage colony-stimulating factor (CSF2), and nuclear factor kappa-B (NF-κβ) to identify the effective therapeutic interventions. , Recently, a low dose of 5 mg/kg Nanoligomer SB_NI_111, a combination treatment targeting NF-κβ and TNFR1, has been shown to significantly reduce inflammation in mouse hippocampus in an LPS-induced neuroinflammation …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations